Implementasi Ice Breaking untuk Menciptakan Kesiapan Belajar dan Pembelajaran yang Menyenangkan pada Anak Usia Dini - yenda puspita puspita (Journal on Education, 2023)
Readiness to learn and fun learning are important factors to achieve learning objectives. If children learn to feel fun, then the teacher will be easy to convey the subject matter, and the child will also respond to every activity in learning appropriately. But in reality, children feel learning and learning is still not fun, both physically and psychologically. If the condition of the child is like this, it is not ideal if the teacher directly provides materials and tasks that must be done by the child. Therefore, teachers can use ice breaker to help children feel fun when learning takes place. This study aims to determine the implementation of Ice Breaking to create learning readiness and fun learning at an early age through qualitative descriptive research. In this study, it is expected to have a positive influence in motivating educators in providing the best children's learning activities for children, because early childhood educators are not only useful but must be able to be an inspiration and motivator for their students. The results of this study reveal that the implementation of ice breaking can create learning readiness and fun learning at an early age, so that they do not feel bored and bored during the learning process. Therefore, it can be said that the implementation of ice breaking in fun learning can overcome the boredom of children, so that learning activities can be more effective.